THE EXPLORATION OF PRE-SERVICE EFL TEACHERS' CHALLENGES IN FIELD PRACTICUM - Pasaka, Rainal Wempi (2014)
This study investigates challenges that six pre-service EFL teachers of a Bachelor of Education (Sarjana Pendidikan) program experienced in conducting field practicum. This study employs a qualitative research design, especially a phenomenological approach. Data were gathered by means of in-depth interviews. The interview data were then scrutinized and codified, respective to their emergent themes through thematic analysis procedures (Merriam, 1988 in Emilia, 2007, p. 84). The findings indicated that field practicum was colored with challenges related to lesson preparation, challenges related to classroom management, and challenges related to communication breakdown. The study concludes with a justification that it is recommended for teacher preparation programs to provide pre-service teachers with robust theoretical frameworks in designing an instruction, practical experience in classroom management, profound knowledge of English language, and strong confidence in teaching. In addition, teacher preparation programs are endorsed to formally inform mentor teachers as to their roles and responsibilities in the practicum. Keywords: Pre-service Teachers, Teacher Preparation Programs, Field Practicum Penelitian ini mengkaji kesulitan-kesulitan yang dihadapi oleh enam calon pendidik EFL (Bahasa Inggris sebagai Bahasa Asing) dari program Sarjana Pendidikan dalam melaksanakan program latihan profesi. Penelitian ini menggunakan desain kualitatif, khususnya menggunakan pendekatan fenomenologi. Data dikumpulkan dengan menggunakan interviu mendalam. Data yang diperoleh dengan menggunakan interviu kemudian dianalisis dan dikodefikasi, berdasarkan tema yang muncul dengan menggunakan prosedur analisis tematik (Merriam, 1988 dalam Emilia, 2007, hal. 84). Hasil penelitian ini menunjukkan bahwa program pelatihan profesi diwarnai dengan kesulitan terkait persiapan pengajaran, kesulitan terkait manajemen kelas, dan kesulitan terkait komunikasi. Penelitian ini ditutup dengan justifikasi bahwa program persiapan guru perlu menyiapkan calon pendidik dengan landasan teori yang kuat dalam mendesain pelajaran, pengalaman praktis dalam manajemen kelas, pengetahuan yang luas mengenai bahasa Inggris, dan kepercayaan diri yang tinggi dalam mengajar. Program persiapan guru juga perlu menginformasikan secara formal kepada guru pamong mengenai peranan dan tanggung jawab mereka di dalam program latihan profesi. Kata kunci: calon pendidik, program persiapan guru, program latihan profesi